Judicialization of economic and monetary union: between a rock and a soft place? - Matos, Nuno Albuquerque (2021)
The European Central Bank has been active since the sovereign debt crisis that struck European Union Member States by putting in place several asset-purchasing programmes such as Outright Monetary Transactions and Public Sector Purchase Programme. As much as these decisions have proven the pivotal importance of this institution within the monetary union, they have also spurred controversy on potentially having exceeded the competences attributed to the Union. The german federal constitutional court heard challenges to both and requested the Court of Justice to decide on their validity within the framework of a preliminary ruling. The decision of the former court to declare the Public Sector Purchase Programme ultra vires -in this way countering the preliminary ruling decision- as well as its argumentation could produce many institutional consequences to both the European Central Bank and Court of Justice of the European Union. Finally, it has shown the limits of European Union integration and will inevitably propel discussions on which way to go in the future: It is time for this discussion to come out from courtrooms into the public sphere.